2005
DOI: 10.1093/jac/dki325
|View full text |Cite
|
Sign up to set email alerts
|

Activity of amine oxide against biofilms of Streptococcus mutans: a potential biocide for oral care formulations

Abstract: Amine oxide showed high potential for controlling early biofilms caused by periodontal bacteria. Further investigations should be carried out, particularly on the potential toxicity of amine oxide and its efficacy in complex formulations for oral care products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The preparation of S. mutans biofilms S. mutans biofilms [UA140::φ (mutAp-mrfp1)] were formed on saliva-coated hydroxyapatite discs; to grow the S. mutans biofilms, a technique described by Fraud et al was modified [21] S. mutans was cultured on sintered circular ceramic HA disks (9.8 mm in diameter×1.5 mm in height; Clarkson Chromatography Products, South Williamsport, PA, USA) that had been incubated with saliva from rats that had not been immunized. The saliva to cultivate the biofilms was pre-filtered through a 5-μm and then a 0.45-μm filter (Fisher Scientific, Loughborough, UK).…”
Section: The Adherence Inhibition Assaymentioning
confidence: 99%
“…The preparation of S. mutans biofilms S. mutans biofilms [UA140::φ (mutAp-mrfp1)] were formed on saliva-coated hydroxyapatite discs; to grow the S. mutans biofilms, a technique described by Fraud et al was modified [21] S. mutans was cultured on sintered circular ceramic HA disks (9.8 mm in diameter×1.5 mm in height; Clarkson Chromatography Products, South Williamsport, PA, USA) that had been incubated with saliva from rats that had not been immunized. The saliva to cultivate the biofilms was pre-filtered through a 5-μm and then a 0.45-μm filter (Fisher Scientific, Loughborough, UK).…”
Section: The Adherence Inhibition Assaymentioning
confidence: 99%
“…A number of authors suggest that biofilm formed over an extensive period of time has increased resistance to antimicrobial substances (20)(21)(22)(23)(24)(25)(26), while others have reported that the age of the biofilm does not enhance resistance to disinfectants (27). Increased extrapolymeric substances and biofilm thickness over time are reported by some to enhance resistance to disinfectant agents (18,28).…”
mentioning
confidence: 99%
“…The bacteriostatic and bactericidal activity of AO on several microorganisms has recently been reported (10,11). AO has been shown to possess anti-bacterial function, and to reduce oral streptococcal plaque and biofilm formation.…”
Section: Chapter 3 Research Objectivesmentioning
confidence: 99%
“…While caustic to fungal and bacterial pathogens, sodium hypochlorite is also very abusive to intraoral tissues and may affect denture base chromaticity when not rinsed completely following application. Fraud, et al has stated in previous projects that low concentrations of AO are safe for intraoral tissues, and even safe for intraoral use and application (10,11).…”
Section: Effect Of Ao On Adherence Of C Albicans To Pmma Discsmentioning
confidence: 99%
See 1 more Smart Citation